Rapid assessment of expansion of nursing, paramedical and public health education and it?s implication on quality of education - Talukder, Md HK; Nazneen, R; Hossain, Md Z; Akther, N; Chowdury, IJ; Parvin, IA (Journal of Institute of Medicine Nepal, 2013)
Introduction: Bangladesh is facing many challenges in health care that are similar to other developing countries. In Bangladesh standard of paramedical, nursing, pharmacy and public health education are expanding rapidly which needs to call for assessment and evaluation to be up to date in the respective fields. Study aims to assess the expansion of Nursing, Paramedical & Public health Education in Govt. & non Govt. sectors & its implication on quality of education. Methods: This was a descriptive type of cross sectional explorative study, conducted among the teachers and student of different institutes. Questionnaire was developed and a FGD was done. Then the data was analyzed. Results: At present situation, the numbers of non govt. organizations are more than govt. organizations (127 vs. 85). SWOT analyses showed the overall strength of the institutions were the scope for further improvements and the political commitments for expansion. Weaknesses lie in the lack of adequate infrastructure, suboptimal technical and laboratory facilities and teaching staffs. Opportunities were, increasing demand and provision of jobs at home and abroad. Possible threats were loss of quality services, recognition and registration of the institutes. Regarding the overall organization of the courses, 43% of the students voted as good and 100% of the teachers showed positive opinion. Regarding the teaching-learning procedure, 41% of the teachers strongly agreed about the perfect selection of the students. 48.3% teachers agreed about the adequacy of the number of teachers. 47.8% students also agreed with the competency of the teachers. Nearly one third teachers as well as students agreed about the good physical environment of the institute. About 35% and 36% of the teachers and the students respectively agreed about the transparency of the assessment systems. Conclusions: Present Bangladesh Govt. has implemented various initiatives regarding health sector reform. Proper funding, management, monitoring and evaluation can improve present situation and thus help in the development of better institutional output. DOI: http://dx.doi.org/10.3126/joim.v34i3.8912 Journal of Institute of Medicine, December, 2012; 34:21-27